Gestational Trophoblastic Neoplasia With Urinary System Metastasis: A Single Center Experience - Cheng, Hongyan; Yang, Junjun; Ren, Tong; Zhao, Jun; Feng, Fengzhi; Wan, Xirun; Xiang, Yang (Frontiers in Oncology, 2020)
Background: Gestational trophoblastic neoplasia (GTN) with urinary system metastasis is rare. There is limited information about this situation. This study aimed to analyze clinical features, prognostic factors and survival outcomes of patients with metastasis to the urinary system arising from GTN. Methods: Medical records of 53 consecutive GTN patients with urinary system metastases and were treated at Peking Union Medical College Hospital (PUMCH) between 1990 and 2018 were reviewed. Kaplan-Meier survival analysis was used to describe the overall survival. Prognostic factors were identified using univariate and multivariate analyses. Results: Fifty-three GTN patients with urinary tract metastasis were identified in our institution. The mean age of patients was 30.8 years (range, 23-53 years). Thirty six (67.9%) patients achieved complete remission (CR), and the remaining 17 (32.1%) showed progressive disease. The 5-year overall survival rate of the entire cohort was 78.4%. Age ≥ 40 years was an independent risk factor for prognosis (HR 12.353, 95% CI 2.203-69.261, P = 0.004). Previous failed chemotherapy history (P = 0.040) and the presence of brain and/or liver metastases (P = 0.024) significantly influenced the survival of GTN patients with urinary tract system metastasis. Conclusion: GTN with urinary tract metastasis is a rare condition. Patients with different metastatic sites have different CR rates and prognoses. Therefore, individualized strategies should be considered for patients with different metastatic sites. Urinary system metastasis is probably not a prognostic factor in GTN patients. Patients aged ≥ 40 years, those who previously failed multidrug chemotherapy, and those who presented brain and/or liver metastases showed a significantly adverse outcome.